Onset and duration of action of lokivetmab in a canine model of IL‐31 induced pruritus. Issue 6 (8th April 2021) - Fleck, Timothy J.; Norris, Lori R.; Mahabir, Sean; Walters, Rodney R.; Martinon, Olivier; Dunham, Steven A.; Gonzales, Andrea J.
Abstract : Background: Interleukin (IL)‐31 is a cytokine involved in allergic inflammation which induces pruritus across species including dogs. Using recombinant canine IL‐31 we have developed a model of pruritus in the dog to evaluate onset of action and duration of effect of therapeutic drugs. Objective: To assess the onset of action and duration of effect of lokivetmab (Cytopoint) in the IL‐31‐induced pruritus model. Animals: Twenty‐four purpose‐bred beagle dogs (neutered males, spayed and intact females) 1.5–4.7 years old and weighing between 6 and14 kg. Methods and materials: Randomized, blinded, placebo‐controlled studies were designed to evaluate the antipruritic properties of lokivetmab. Laboratory beagle dogs were given either placebo, 0.125, 0.5 or 2.0 mg/kg lokivetmab, subcutaneously. IL‐31 then was administered to evaluate pruritus 3–5 h post‐placebo or ‐lokivetmab administration as well as one, seven, 14, 28, 42 and 56 days post‐dosing. Pruritus was evaluated over a 2 h window in animals by video monitoring and scored using a categorical scoring system. Results: When animals were given 2.0 mg/kg lokivetmab, a significant reduction in pruritus was observed at 3–4, 4–5 and 3–5 h post‐treatment ( P ≤ 0.0001 ) . When animals were given either 0.125, 0.5 or 2 mg/kg lokivetmab, the duration of effect was dose‐dependent and statistically significant for 14, 28 and 42 days, respectively ( P ≤ 0.0288). Conclusion: These data indicate that a single subcutaneous injection of 2 mg/kg lokivetmab produces a significant suppression of pruritus starting 3 h post‐treatment that can be sustained for 42 days. Abstract : Onset of antipruritic action of lokivetmab in dogs. Laboratory‐bred beagle dogs were dosed subcutaneously with either placebo or lokivetmab at 2.0 mg/kg on Day (D) 0. Approximately 2.5 h post‐dosing, pruritus was induced using canine interleukin (IL)‐31. Animals were observed for pruritic behaviours for a total of 2 h (3–5 h post‐treatment with placebo or lokivetmab). Observations were presented per hour (3–4 h, 4–5 h and 3–5 h post‐treatment with placebo or lokivetmab). Data are expressed as least square mean (LSM) ± standard error of mean (SEM). Treatment comparisons at each time point were conducted at the two‐sided α = 0.05 significance level (* P < 0.0001). Résumé: Contexte: L'interleukine (IL)‐31 est une cytokine impliquée dans l'inflammation allergique qui induit le prurit pour toutes les espèces dont le chien. En utilisant un IL‐31 recombinant nous avons développés un modèle de prurit chez le chien pour évaluer le début de l'action et la durée des effets des traitements. Objectifs: Déterminer le début d'action et la durée de l'effet du lokivetmab (Cytopoint) dans le modèle de prurit induit par IL‐31. Sujets: Vingt quatre chiens beagle de reproduction (mâles castrés, femelles stérilisées et entières) 1, 5 ‐ 4, 7 ans et pesant de 6 à 14 kg. Méthodes: Les études contrôlées contre placebo, en aveugle, randomisées ont été étudiées pour évaluer les propriétés antiprurigineuses du lokivetmab. Les chiens beagle de laboratoire ont été attribués aux goupes placebo, 0.125, 0.5 ou 2.0 mg/kg de lokivetmab en sous‐cutané. L'IL‐31 a ensuite été administrée pour évaluer le prurit 3‐5h après administration de lokivetmab ou de placebo ainsi que un, sept, 14, 38, 42 et 56 jours après dosage. Le prurit était évalué sur une fenêtre de 2h chez les animaux par monitoring vidéo et scoring utilisant un système d'évaluation catégorielle. Résultats: Quand les sujets ont reçu 2.0 mg/kg de lokivetmab, une diminution significative du prurit était observée à 3‐4, 4‐5 et 3‐5h post traitement ( P ≤ 0.0001 ) . Quand les animaux recevaient soit 0.125 soit 0.5 ou 2 mg/kg de lokivetmab, la durée de l'effet était dépendant de la dose et statistiquement significatif, respectivement, pour 14, 28 et 42 jours ( P ≤ 0.0288). Conclusion: Ces données indiquent qu'une unique injection sous‐cutanée de 2 mg/kg de lokivetmab produit une suppression significative du prurit dès 3h après traitement et persiste pendant 42 jours. RESUMEN: Introducción: la interleuquina (IL)‐31 es una citoquina involucrada en la inflamación alérgica que induce prurito en todas las especies, incluidos los perros. Utilizando IL‐31 canina recombinante, hemos desarrollado un modelo de prurito en el perro para evaluar el inicio de la acción y la duración del efecto de los fármacos terapéuticos. Objetivo: evaluar el inicio de la acción y la duración del efecto de lokivetmab (Cytopoint) en el modelo de prurito inducido por IL‐31. Animales: Veinticuatro perros Beagle de laboratorio (machos castrados, hembras esterilizadas e intactas) de 1, 5 a 4, 7 años y con un peso de entre 6 y 14 kg. Métodos: se diseñaron estudios aleatorios, ciegos y controlados con placebo para evaluar las propiedades antipruriginosas del lokivetmab. A los perros Beagle de laboratorio se les administró placebo, 0, 125; 0, 5 o 2, 0 mg/kg de lokivetmab por vía subcutánea. Luego se administró IL‐31 para evaluar el prurito 3‐5 h después de la administración de placebo o lokivetmab, así como a uno, siete, 14, 28, 42 y 56 días después de la dosificación. El prurito se evaluó durante una ventana de 2 h en animales mediante monitorización por vídeo y se puntuó utilizando un sistema de puntuación categórico. Resultados: cuando se administró a los animales 2, 0 mg/kg de lokivetmab, se observó una reducción significativa del prurito a las 3‐4, 4‐5 y 3‐5 h después del tratamiento ( P ≤ 0, 0001). Cuando se administró a los animales 0, 125; 0, 5 o 2 mg/kg de lokivetmab la duración del efecto fue dependiente de la dosis y estadísticamente significativa durante 14, 28 y 42 días, respectivamente ( P ≤ 0, 0288). Conclusión: estos datos indican que una sola inyección subcutánea de 2 mg/kg de lokivetmab produce una supresión significativa del prurito a partir de las 3 h posteriores al tratamiento que se mantiene durante 42 días. Zusammenfassung: Hintergrund: Interleukin (IL)‐31 ist ein Zytokin, welches bei der allergischen Entzündung involviert ist und Juckreiz bei allen Spezies wie auch beim Hund auslöst. Wir haben beim Hund ein Juckreiz Modell entwickelt, wobei wir eine rekombinante Form von caninem IL‐31 verwendet haben, um den Wirkungseintritt und die Dauer der Wirkung dieser therapeutischen Medikamente zu evaluieren. Ziel: Die Beurteilung des Wirkungseintritts und der Wirkungsdauer von Lokivetmab (Cytopoint) beim durch IL‐31 induzierten Juckreizmodell. Tiere: Vierundzwanzig zu diesem Zweck gezüchtete Beagles (kastrierte Rüden, kastrierte und intakte Hündinnen), im Alter von 1, 5 – 4, 7 Jahren, mit einem Gewicht zwischen 6 und 14 kg. Methoden: Es wurden randomisierte, geblindete, Plazebo‐kontrollierte Studien designed, um die juckreizstillenden Eigenschaften von Lokivetmab zu evaluieren. Laborbeagles wurde entweder Plazebo oder 0, 125; 0, 5 oder 2, 0 mg/kg Lokivetmab subkutan verabreicht. IL‐31 wurde verabreicht, um den Juckreiz 3‐5h Post‐Plazebo oder ‐Lokivetmab Verabreichung zu evaluieren, sowie nach einem, sieben, 14, 28, 42 und 56 Tage post‐Administration. Der Juckreiz wurde über ein 2‐stündiges Fenster evaluiert, wobei die Tiere mittels Videoüberwachung und mit Hilfe eines kategorischen Systems bewertet wurden. Ergebnisse: Wenn den Tieren 2, 0 mg/kg Lokivetmab verabreicht wurde, konnte eine signifikante Reduktion des Pruritus 3‐4, 4‐5 und 3‐5 h nach der Behandlung ( P ≤ 0, 0001) beobachtet werden. Wenn den Tieren entweder 0, 125; 0, 5 oder 2 mg/kg Lokivetmab verabreicht wurde, war die Wirkungsdauer Dosis‐abhängig und für 14, 28 bzw 42 Tage statistisch signifikant ( P ≤ 0, 0288). Schlussfolgerung: Diese Ergebnisse zeigen, dass eine einzige subkutane Injektion von 2 mg/kg Lokivetmab eine signifikante Unterdrückung des Juckreizes bewirkt, welche 3h nach der Administration beginnt und 42 Tage lang anhält. 要約: 背景: インターロイキン (IL)‐31 はアレルギーによる炎症に関与するサイトカインであり、犬を含む様々な種の掻痒を誘発する。我々は、イヌ IL‐31 を用いて、犬の掻痒モデルを開発し、治療薬の作用発現および効果持続時間を評価した。 目的: 本研究の目的は、IL‐31誘発性掻痒モデルにおけるロキベトマブ (サイトポイント) の作用発現および効果持続時間を評価することであった。 被験動物: 1.5˜4.7歳、体重6˜14kgの24頭の実験ビーグル犬 (去勢済みオス、去勢済みメス、未避妊メス) 。 方法: ロキベトマブの抗掻痒特性を評価するため、無作為化盲検プラセボ対照試験を実施した。実験用ビーグル犬にプラセボ、0.125、0.5または2.0mg/kgのロキベトマブを皮下投与した。その後、IL‐31を投与し、プラセボまたはロキベトマブ投与3˜5時間後、および投与1日後、7日後、14日後、28日後、42日後、56日後の掻痒を評価した。掻痒は、ビデオモニタリングにより動物を2時間評価し、カテゴリカルスコアリングシステムを用いて点数化した。 結果: 被験動物に2.0 mg/kgのロキベトマブを投与した場合、掻痒の有意な減少が3‐4、4‐5および3‐5時間後に観察された (P≦0.0001) 。動物に0.125、0.5または2mg/kgのロキベトマブを投与した場合、効果の持続期間はそれぞれ14日、28日および42日で用量依存的であり、統計的に有意であった (P≦0.0288) 。 結論: これらのデータは, 2mg/kgのロキベトマブを単回皮下注射することで, 治療後3時間後から掻痒が有意に抑制され, その効果は42日間持続することを示している。 摘要: 背景: 白细胞介素(IL)‐31是一种参与过敏性炎症的细胞因子, 可在包括犬等多物种体内诱导瘙痒。使用重组犬IL‐31, 我们开发了犬瘙痒模型, 以评价治疗药物的起效时间和作用持续时间。 目的: 评估洛基维特单抗(赛妥敏)在IL‐31诱导瘙痒模型中的起效时间和作用持续时间。 动物: 24只专门饲养的比格犬 (去势雄性、切除卵巢和完整雌性), 1.5‐4.7岁, 体重6‐14 kg。 方法: 随机、设盲、安慰剂对照研究旨在评价洛基维特单抗的止痒特性。实验室比格犬经皮下给予安慰剂、0.125、0.5或2.0 mg/kg 洛基维特单抗。然后给予IL‐31, 以评价安慰剂或洛基维特单抗给药后3‐5h以及给药后1、7、14、28、42和56天的瘙痒。通过视频监测在2h窗口内评价动物的瘙痒, 并使用分类评分系统进行评分。 结果: 当给予动物2.0 mg/kg 洛基维特单抗时, 在给药后3‐4、4‐5和3‐5 h观察到瘙痒显著减轻(P≤0.0001)。当给予动物0.125、0.5或2 mg/kg 洛基维特单抗时, 作用持续时间呈剂量依赖性, 分别为14、28和42天, 具有统计学显著性(P≤0.0288)。 结论: 这些数据表明, 2 mg/kg 洛基维特单抗单次皮下注射给药后3h开始显著抑制瘙痒, 并能持续42天。 Resumo: Contexto: A interleucina (IL) ‐31 é uma citocina envolvida na inflamação alérgica que induz prurido em várias espécies, incluindo cães. Utilizando IL‐31 canina recombinante, desenvolvemos um modelo de prurido em cães para avaliar o início da ação e a duração do efeito de drogas terapêuticas. Objetivo: Avaliar o início de ação e a duração do efeito do lokivetmab (Cytopoint) no modelo de prurido induzido por IL‐31. Animais: Vinte e quatro cães beagle criados para fins específicos (machos castrados, fêmeas esterilizadas e intactas) com 1, 5–4, 7 anos de idade e pesando entre 6 e 14 kg. Métodos: Estudos randomizados, cegos e placebo‐controle foram elaborados para avaliar as propriedades antipruriginosas do lokivetmab. Os cães beagle de laboratório receberam placebo, 0, 125, 0, 5 ou 2, 0 mg/kg de lokivetmab, por via subcutânea. A IL‐31 foi então administrada para avaliar o prurido 3–5 h após a administração de placebo ou lokivetmab, bem como um, sete, 14, 28, 42 e 56 dias após a administração. O prurido dos animais foi avaliado através de monitoramento por vídeo ao longo de uma janela de 2h e pontuado usando um sistema de pontuação categórica. Resultados: Quando os animais receberam 2, 0 mg/kg de lokivetmab, uma redução significativa do prurido foi observada em 3‐4, 4‐5 e 3‐5h após o tratamento ( P ≤ 0, 0001). Quando os animais receberam 0, 125, 0, 5 ou 2 mg/kg de lokivetmab, a duração do efeito foi dependente da dose e estatisticamente significativa durante 14, 28 e 42 dias, respetivamente ( P ≤ 0, 0288). Conclusão: Esses dados indicam que uma única injeção subcutânea de 2 mg/kg de lokivetmab produz uma supressão significativa do prurido começando 3 horas após o tratamento, que é mantida por 42 dias.